Autonomy, competence, and social relatedness: key factors for explaining the decline in students’ intrinsic motivation in math - Reschke, Katharina; Kuhn, Hans Peter; Kling, Ines; Buhl, Monika (Developmental psychology, 2025)
This study aimed to further our understanding of the predictors of the decline of students’ intrinsic motivation in math in secondary school. Based on cognitive evaluation theory and stage-environment fit theory, we tested the hypotheses that changes in the three basic needs (competence, autonomy, and relatedness) can explain interindividual differences in the decline of students’ intrinsic motivation. A sample of N = 337 German students (t1: M = 11.33 years, SD = 0.59) was followed for 5 years from the end of Grade 5 to the end of Grade 10. Students gave self-reports on their intrinsic motivation in math, perceived competence, autonomy, and social relatedness. Latent change score models showed declines in students’ intrinsic motivation in math over the period of time. Moreover, we found interindividual differences in changes of students’ intrinsic motivation. Furthermore, decreases in students’ perceived competence, autonomy, and social relatedness significantly predicted the decline in students’ intrinsic motivation. Therefore, the present findings provide suggestions as to how the decline of students’ intrinsic motivation in secondary school could be explained. Implications for future research as well as for educational practice in schools are discussed. (PsycInfo Database Record (c) 2025 APA, all rights reserved)
Gesehen am 09.12.2025